Avaliação dos parâmetros espermáticos de zangões de abelhas africanizadas apis mellifera l. No semiárido nordestino do brasil - Morais, Lucas da Silva (2019)
The present study aims to characterize the spermatozoa of Africanized bees (Apis mellifera L.) in the semiarid region, produced during the harvest and off - season. The drones were obtained during the harvest period in the months of March to June of 2018 and of off-season in the months of October and December of 2018 at the Experimental Station of UFERSA. The drones were considered mature when they presented complete inversion and presence of semen in the tip of the endophallus. Semen collection was done by manual penile eversion technique. The following sperm parameters were evaluated: motility, membrane integrity, concentration and morphology. It was observed that the africanized bee bees evaluated in the harvest period had an average motility of 85.6 ± 8.1%, a viability of 80.2 ± 10% and a concentration of 3.8 ± 1.2x106 spermatozoa. On the other hand, the mean values were 52 ± 21.2%, 70.9 ± 12.8% and 3 ± 1.1x106 spermatozoa. The spermatozoa evaluated in the crop showed more abnormalities in their morphology, having an average percentage of spermatozoa with coiled tail of 64.9%, broken tail 3.6% and double tail 1.1% in relation to those evaluated in the off season that had an average percentage of spermatozoa with coiled tail of 60.7%, broken tail 2% and double tail 1,1%. The spermatozoa evaluated in the harvest period presented motility, viability and concentration superior to the spermatozoa evaluated in the off season. However, in relation to the morphology, the spermatozoa of the crop, presented more morphological defects, being the coiled tail the main one, when compared with those evaluated in the off season